Coleoptera diversity (Arthropoda: Insecta) and soil properties under soil management systems in the highlands of Santa Catarina state, Brazil Diversidade de Coleoptera (Arthropoda: Insecta) e atributos edáficos em sistemas de uso do solo no Planalto Catarinense - Pompeo P.N.* (2016)
Beetles (Coleoptera) are distributed in different areas and soil depths and they are important executors of several environmental services. Their study is an excellent tool to elucidate the effects of human disturbance on biodiversity and ecosystem functions. The aim of this study was to evaluate the diversity of Coleoptera families in different land use systems (LUS) and their relationship with soil properties. The systems were: native forest (NF), eucalyptus plantations (EP), pasture (PA), crop-livestock integration (CLI) and with no-tillage crop (NT). The samples were collected in sampling grid of 3 × 3 points apart from each other at 30 m, in the periods of winter and summer, in three municipalities of the highlands of Santa Catarina state. Edaphic invertebrates were collected by methods of monoliths (Tropical Soil Biology and Fertility - TSBF) and Pitfall traps. In the same points samples soil was collected to determine the physical and chemical properties. The multivariate statistical analysis was used to the community composition, and the environmental variables were considered as explanations. 1.437 individuals were collected, the Staphylinidae, Carabidae and Scarabaeidae families was the most representative. The EP and NT systems showed the greatest diversity in accordance with the Shannon-Wiener index (H). The principal component analysis showed distinction in the distribution of invertebrates between different LUS. Soil properties contributed to explain this variation, having influence on the diversity of Coleoptera families, highlighting the attributes organic matter and porosity that favored the greatest abundance of families in NF.